Pembentukan Karakter Melalui Pendidikan Agama Islam - Ainiyah, Nur (Al-Ulum, 2013)
This writing is presenting about the role of Pendidikan Agama Islam (PAI) lesson toward students. Pendidikan Agama Islam (PAI) is one of the most importances pilar of character education. Character education will build well, if it is started from cultivating religious sense of students, therefore, PAI lesson become one of supporting lesson of character education. Through PAI teaching and learning, the students is taught belief of God as the basic of their religion, taught al quran and hadits as their way of life, taught fiqih as law signs in doing Islam teaching, taught Islam history as a good life example, and taught ethica as the way of human character.